Invisible Ink - Abigail Ralph (Caribbean Studies Students' Union, 2022)
There is a gap in academic literature that highlights the perspectives of Canadian-Caribbean individuals that navigate both poverty and the stigma of limited access to resources necessary for livelihood in Canada. By employing the intersecting identities of Low-Income and (un)documentation, this poem aims to deconstruct the stereotypical expectations of Canadian-Caribbean immigrants. What does an impoverished Canadian-Caribbean immigrant look like once we've disregarded our representativeness heuristic? They now may be the straight-A student in your class or that lady that never seems to wear an uncoordinated outfit - or perhaps your lecturer or community organizer who has an undying passion for 19th-century opera. By mobilizing this idea, this poem seeks to encourage the reader to reconsider our pre-conceived notions of an (un)documented, impoverished Canadian-Caribbean individual. Similarly, this poem challenges the notion that to exist, is contingent on external perceptions. A tree in the Northwest Territories may exist unknowingly to us and still be able to blow gracefully in the wind.